تحديد أربعة أنواع من الشريطيّات كاذبة المحاجم الطفيلية في لمعة أمعاء أسماك الكارب العادي (Cyprinus Carpio L.)في مزرعة شطحا (الغاب- سوريا) - سلمان, حسن (Latakia University Journal -Biological Sciences Series, 2019)
شملت الدراسة 142 سمكة كارب عادي بأعمار من 35 يوم حتّى سنة، أخذت العيّنات بشكل عشوائيّ شهريّاً من مزرعة شطحا (الغاب) خلال العام 2006. تمّ عزل وتصنيف ثلاثة أنواع من الشريطيات الطفيلية تنتمي للجنس. Bothriocephalus (B.) هي: B.acheilognathi, B.opsariichthydis and B. claviceps إضافة إلى نوع رابع ينتمي للجنس Eubothrium (E.) هو E. salvelini تواجدت هذه الديدان في لمعة الأمعاء. تباينت الأنواع المعزولة في نسب إصابتها( خمجها) للأسماك وكان النوع B.acheilognathi أكثر انتشاراً بنسبة إصابة بلغت 3,52% وشدة إصابة بلغت 4,4 دودة/سمكة. سّجلت هذه الأنواع الطفيلية لأوّل مرة في مزارع أسماك شطحا في هذه الدراسة، كما لم تبد هذه الطفيليات علاقة مباشرة مع بعض المؤشرات البيئية، فقد ظهرت بشكل متفّرق خلال أشهر السنة وفصولها. This study is performed on 142 carp fish (Cyprinus carpio L.) aged between 35 days and one year. Samples are collected from Shatha Fish Farm randomly and on a monthly basis. Three parasitic species of Cestoda helminthes belonging to genus Bothriocephalus (B.) have benn isolated and classified. These include: B.acheilognathi, B. opsariichthydis and B.claviceps, and a fourth parasitic species belonging to genus Eubothrium (E.), which is E. salvelini, deposited in intestinal lumen. All 4 tapeworms varied in the rates of their infection of fish. B.acheilognathi is the most abundant one with an infection rate of 3, 52% and infection intensity of 4,4 worms/fish. In this study, these parasitic species have been recorded for the first time on Shatha Fish Farm. They have not shown a direct relationship with some environmental factors, and their occurrence has been sporadic.